Isolation and Characterization of a Phosphorus-Solubilizing Bacterium from Rhizosphere Soils and Its Colonization of Chinese Cabbage (Brassica campestris ssp. chinensis) - Wang, Zhen; Xu, Guoyi; Ma, Pengda; Lin, Yanbing; Yang, Xiangna; Cao, Cuiling (Frontiers in Microbiology, 2017)
Phosphate-solubilizing bacteria (PSB) can promote the dissolution of refractory phosphorus (P) in soil, enhancing the availability of soluble P. Thus, their application can reduce the consumption of fertilizer and aid in sustainable agricultural development. From the rhizosphere of Chinese cabbage plants grown in Yangling, we isolated a strain of PSB (YL6) with a strong ability to dissolve P and showed that this strain promoted the growth of these plants under field conditions. However, systematic research on the colonization of bacteria in the plant rhizosphere remains deficient. Thus, to further study the effects of PSB on plant growth, in this study, green fluorescent protein (GFP) was used to study the colonization of YL6 on Chinese cabbage roots. GFP expression had little effect on the ability of YL6 to grow and solubilize P. In addition, the GFP-expressing strain stably colonized the Chinese cabbage rhizosphere (the number of colonizing bacteria in the rhizosphere soil was 4.9 lg CFU/g). Using fluorescence microscopy, we observed a high abundance of YL6-GFP bacteria at the Chinese cabbage root cap and meristematic zone, as well as in the root hairs and hypocotyl epidermal cells. High quantities of GFP-expressing bacteria were recovered from Chinese cabbage plants during different planting periods for further observation, indicating that YL6-GFP had the ability to endogenously colonize the plants. This study has laid a solid and significant foundation for further research on how PSB affects the physiological processes in Chinese cabbage to promote plant growth.